The Influence Of Polaroid Photo Media In Teaching Speaking Skills To Students Of The Ash-Habul Yamin Taram, Lima Puluh Kota,West Sumatera - Isnani, Arina; Febrianta, Rita; Hasanah, Nur; Rizal, Eka (Universitas Pahlawan Tuanku Tambusai, 2024)
As for the results of the research, there is the influence of Polaroid photo media in teaching speaking skills to seventh semester students at the Institute, Ash-Habul Yamin Taram, Lima Puluh Kota,west Sumatera. and the extent of its influence. is about 50%. Significance score or (2-Tailed) Sig. In the table it is 0.032 and this result is smaller than 0.05. Therefore, the reverse hypothesis is null (Ho), and the accepted alternative hypothesis is (Ha).This shows that there is an average difference between the experimental class which uses the Polaroid image method in teaching speaking skills and the control class which uses the Polaroid image method in teaching speaking skills and the control class which does not use the Polaroid image method in teaching speaking skills.